A case study comparing the completeness and expressiveness of two industry recognized ontologies. (January 2021) - Quinn, Caroline; McArthur, J.J.
Highlights: Comparison of Brick and Project Haystack ontology for use with Smart Building applications. Qualitative document review of ontologies. Quantitative expressiveness and completeness assessment of ontologies. Abstract: Enabling Smart Building applications will help to achieve the ongoing efficient commissioning of buildings, ultimately attaining peak performance in energy use and improved occupant health and comfort, at minimum cost. For these technologies to be scalable, ontology must be adopted to semantically represent data generated by building mechanical systems, acting as conduit for connection to Smart Building applications. As the Building Automation System (BAS) industry considers Brick and Project Haystack ontologies for such applications, this paper provides a quantitative comparison of their completeness and expressiveness using a case study. This is contextualized within the broader set of ontological approaches developed for Smart Buildings, and critically evaluated using key ontology qualities outlined in literature. Brick achieved higher assessment values in completeness and expressiveness achieving 59% and 100% respectively, as compared to Haystacks 43% and 96%. Additionally, Brick exhibited five of six desirable qualities, where Haystack exhibited only three. Overall, this critical analysis has found Brick to be preferable to Haystack but still lacking in completeness; to overcome this, it should be integrated with other existing ontologies to serve as a holistic ontology for the longer- term development of Smart Building applications. These will support innovative approaches to sustainability in building operations across scales and as next- generation building controls and automation strategies.